Exploring the digital divide in underserved communities in rural Mpumalanga, South Africa - Shandukani, Linda (University of the Witwatersrand, Johannesburg, 2024)
This research report explored the digital divide in underserved communities in rural Mpumalanga, South Africa, focusing on how owning a smartphone can help bridge the gap. Despite the widespread use of digital technology, financial constraints and limited digital literacy continue to create disparities, especially among marginalised populations. The study employed a qualitative research design, primarily through eight in- depth interviews, to explore how smartphones can impact digital inclusion and overall quality of life in these communities. The findings reveal a digital divide, particularly among young Black individuals, due to barriers in smartphone and internet accessibility. While ease of access to technology can enhance social and economic capital, challenges such as pricing and infrastructure limitations exacerbate disparities, perpetuating cycles of poverty and marginalisation.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, In the Faculty of Commerce, Law and Management, WITS Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Digital Divide; nderserved communities; Smartphone ownershi; SDG-9: Industry, innovation and infrastructure; SDG-11: Sustainable cities and communities